Personality According to Personality Psychology - Nur Amim (Formosa Journal of Social Sciences (FJSS), 2022)
Personality psychology is a scientific study that aims to understand individual personalities as individual beings who have unique traits with other people. The uniqueness can be seen from the behavior, thoughts, feelings, and motivations that exist within each person. Nevertheless, these differences can also show certain patterns which then have similarities with other people. Modern psychology separates God from human subjective experience. Subjective-religious experience is still seen as unscientific. In a scientific perspective, it must meet logical-rational-empirical standards. As the heir to modernism, psychology is also under the scientific method as other sciences. Therefore, the development of modern psychology is supported by three main pillars. First, psychology is universal, second, based on empirical methods, third, research as a locomotive of progress. The method in this paper is literature review. Literature review is an activity of collecting scientific data, especially in the form of theories, methods, or research that has been done before, both in the form of books, document manuscripts, journals, and others that are already in the library. We found that there are similarities in meaning between character and personality according to modern psychology